Anti-Suffrage Movement and The Woman Patriot journal (1918–1932) in Jelena J. Dimitrijević's travelogue The New World or a Year in America (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In thirty-six chapters of her travelogue The New World or a Year in America, Jelena J. Dimitrijević describes 20th-century America. Through her description of cities, festivities, daily life habits, and visits to universities, lectures and conferences, Jelena Dimitriijević enables us to follow the main area of her interest – women and their position. Apart from personal impressions and descriptions, in her travelogue, Jelena Dimitrijević also comments on periodical materials such as newspaper articles, pamphlets, and advertisements, and so provides an insight into the current social issues. The first part of this paper describes the socio-economic circumstances that women live in, while the other part focuses on the Anti-Suffrage Movement, and particularly on the antifeminist journalThe Woman Patriot (1918–1932) and its presence in the travelogue The New World or a Year in America. The last part deals with the social issues addressed by the articles published in The Woman Patriot.
Keywords: The New World or a Year in America; Jelena J. Dimitrijević; Anti-Suffrage Movement; The Woman Patriot journal (1918–1932)